A new plea for time: The significance of museum exhibitions in today’s media landscape - Vestergaard, Vitus (Tidsskrift for Medier, Erkendelse og Formidling, 2016)
Gennem anvendelse af Harold Innis’ begreber time-bias og space-bias undersøger denne artikel betydningen af museumsudstillinger i medielandskabet. Der argumenteres ud fra et medieøkologisk perspektiv for at udstilling bør betragtes som et time-biased medie i et udpræget space-biased samfund. Eftersom museer i højere og højere grad vender sig imod det spatiale, bliver balance et centralt tema. Denne artikel diskuterer også rollen af såkaldt virtuelle udstillinger og konkluderer afslutningsvist, at det er vigtigt at øge opmærksomheden omkring – og forståelsen af – udstillingsmediet, samt at museer bør overveje deres rolle som medieskabere. Based on Harold Innis’ concepts of time-bias and space-bias this article examines the significance of museum exhibitions in the media landscape. From a media ecology perspective, it is argued that the exhibition should be seen as a time-biased medium in a highly space-biased society. Since museums are increasingly turning towards space, balance becomes a central issue. The article also discusses the role of so-called virtual exhibitions and ultimately concludes that increased awareness and appreciation of the exhibition medium is important and that museums should consider their role as media makers.